Síntese, propriedades e investigação estrutural de 1,3-diariltriazenos e complexos com Ni(II), Pd(II), Pt(II) e Hg(II) - Visentin, Lorenzo do Canto (2006)
Although transition metal complexes with nitrogen coordination spheres involving monocatenated 1,3-diarylsubstituted triazenido ligands (ArNNNAr)−, have been investigated in the last decades, the structure of such compounds continues to attract the interest investigatiors. The synthesis of new triazenes derive 1-3-diariltriazenes and reaction with transition metal Ni(II), Pd(II), (Pt) and Hg(II) is the subject of this work. Triazenes are molecules with free electron pairs. These electron pairs can be donors to the transition metal for the formation of coordination complexes. The crystal structure of 3-(4-bromophenyl)-1-(4-nitrophenyl)triazene, 3-(2-flúorophenyl)-1-(4-nitrophenyl)triazene and 1-3-bis(4-azophenyl)triazene, shows that the stereochemistry about the N=N double bond in the diazoamine moiety is trans. Intermolecular interactions were observed in solid state. Treatment of palladium chloride and trans-[Pd(Cl)2(PPh3)2] with two equivalents of 1,3-disubstituted triazenes (RN=N-NHR), derived from 1-3-diariltriazenes, 3-(4-bromophenyl)-1-(4-nitrophenyl)triazenido, 3-(4-clorophenyl)-1-(4-nitrophenyl)triazenido, 3-(2-fluorophenyl)-1-(4-nitrophenyl)triazenido, 1,3-bis(pazophenyl) triazenido and pyridine, except for the reaction with trans-[Pd(Cl)2(PPh3)2], form complexes as deep red crystalline solids which form small crystal block. The palladium complexes exhibit square-plane coordination spheres with trans-1-3-diariltriazenes. A positional disorder effect was observed in (1). The unit cell of complex (2) is formed with two structure isomers. Complex (3) has intermolecular and intramolecular interactions via non-classic hidrogen bonds. The reaction between cis-[Pt(Cl)2(DMSO)2] and two equivalents of 1,3-disubstituted triazenes (RN=N-NHR), derived from 1-3-diariltriazenes, 3-(4-bromophenyl)-1-(4-nitrophenyl)triazenido, 3-(4-clorophenyl)-1-(4-nitrophenyl)triazenido, 3-(4-fluorophenyl)-1-(4-nitrophenyl)triazenido, 3-(2-fluorophenyl)-1-(4-nitrophenyl) triazenido and pyridine, all form complexes. The platinum complexes yield deep red crystalline solids which form small prismatic crystal. The complexes exhibit squareplane coordination with cis and trans 1-3-diariltriazenes. Complex (5) has intramolecular interactions via non-classic hidrogen bonds. The complexes (6), (7) e (8) have intermolecular and intramolecular interactions via non-classic hidrogen bonds. Two more complexes, one with nickel((II), and the other with mercury(II) were caracterized by X-ray crystallography, from red crystals of [NiII(Py)2(PhN2C6H4NNNC6H4R)2] (9) (Py = pyridine; R = 4-azophenyl) and {[HgII(Py)2(PhN2C6H4NNNC6H4R)2]2}n (10) (Py = pyridine; R = NO2). In the (9) we observed the first chelate coordination form of 1-3-bis(4-diazophenyl)triazene. Two triazenido ligands plus two molecules of pyridine are in a cis geometry in the coordination sphere. In (10) tectons {[HgII(Py)2(PhN2C6H4NNNC6H4R)2]2}n are linked in pairs as centrosymmetric dimers through reciprocal metal-2-arene p-interactions. The dimeric units are assembled by translation in the plane ac to unidimensional chains linked through non classical C−H×××O hydrogen bonds.